PENGARUH MODAL INTELEKTUAL TERHADAP NILAI PASAR PERUSAHAAN MELALUI KINERJA KEUANGAN PADA PERUSAHAAN DI BURSA EFEK INDONESIA - Gustini, Sri (Universitas muhammadiyah palembang, 2016)
This study determined the effect of intellectual capital on the market value of the company with the company's financial performance as variable intervening in the agricultural sector companies listed on the Stock Exchange Indonesia (BEI). The sampling technique used is random sampling and data collection techniques employed is documentation. This study employeds series of specification/ diagnostic testing prior to regression such as autocorrelation, multicollinearity, heteroscedasticity test and test coefficient which includes the F test and t test and path analysis (direct and indirect effect). The results reveal that the intellectual capital does not affect the company's financial performance. Moreover, intellectual capital is also not directly influence the company's market value, whereas intellectual capital indirect effect on the market value of the company so that the financial performance as an intervening variable capable of mediating the relationship of intellectual capital to the market value of the agricultural sector companies listed in Indonesia Stock Exchange. Intellectual capital should be evaluated and carried out repairs in the future so that the company can achieve its goals, improve the company's financial performance so that it can respond to increasing the company's market value as well.